Biologically Active Peptides Interacting with the G Protein-Coupled Formylpeptide Receptors - Le, Yingying; Wang, Ji M.; Liu, Xiaolei; Kong, Yan; Hou, Xinwei; Ruan, Lingfei; Mou, Haiwei (Protein and Peptide Letters, 2007)
Leucocytes accumulate at sites of inflammation and microbial infection in response to locally produced chemotactic factors. N-formylpeptides produced by Gram negative bacteria were among the first chemotactic factors structurally defined which signal through G protein-coupled formylpeptide receptor (FPR) and FPR-like 1 (FPRL1) expressed by phagocytic leukocytes in human and in mouse homogogues mFPR and mFPR2. During the past few years, a number of pathogen- and host-derived agonists/antagonists for FPR, FPRL1 and another FPR variant FPR-like 2 (FPRL2) have been identified. Activation of formylpeptide receptors (FPRs) in phagocytic leukocytes by agonists results in increased cell chemotaxis, phagocytosis, and release of pro-inflammatory mediators. Peptide agonists for FPRs have also been shown to possess immune adjuvant activity when injected in mice. In addition, FPR aberrantly expressed on highly malignant human glioblastoma cells promotes tumor cell migration, proliferation and production of vascular endothelial growth factor in response to agonists released by necrotic tumor cells. Therefore, formylpeptide receptor ligands, by interacting with FPRs, play important roles in host defense and in the rapid progression of human glioblastoma.
Keywords: infection